(untitled) (Impetus, 2025)
The general objective of the present study was to analyze the effect of the “to school by bike” CBA modality on physical fitness in boys and girls between 9 and 10 years of age from 3 IED of Bogotá D.C. A prospective study was carried out with a non-ex- perimental longitudinal cohort design, 103 children, 53 CBA participants for the study group (EG) and 51 schoolchildren for the control group (CG) beneficiaries of subsidy and school route made up the sample. Anthropometric data of weight, height, BMI and fat percentage were taken, physical fitness was measured by evaluating the horizontal jump test, Sit and reach and Leger for strength, flexibility and maximum oxygen consumption respectively, data were taken in pretest and posttest phases with a difference of 6 weeks between measurements, time in which the distance traveled by bicycle was followed up, statistically significant differences were obtained p< 0. 05 for the physical fitness variables, determining that the effect of the modality was evidenced to a greater extent in 10-year-old boys and girls. The distance covered by bicycle is a determining factor in the modification of physical fitness.